Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1161/atvbaha.115.305438
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Myeloid GSK3α Attenuates Atherosclerosis and Promotes an M2 Macrophage Phenotype

Abstract: A therosclerosis is the main underlying pathology of cardiovascular disease, which accounts for the majority of deaths in developed nations.1 Myeloid lineage cells are critical mediators in the development of atherosclerosis and account for the majority of a lesion's cellular bulk.2 Within the atherosclerotic lesion, macrophages phagocytose modified lipid particles becoming lipid engorged foam cells. Foam cells exacerbate disease progression through the secretion of proinflammatory cytokines and growth factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 49 publications
3
35
0
Order By: Relevance
“…Theoretically speaking, M2 macrophages should be pro-atherogenic due to their pro-angiogenic effects. However, the emerging understanding of macrophage subsets and their functions in atherosclerotic plaque has led to the consensus that M1 macrophages are pro-atherogenic, while M2 macrophages may promote plaque stability (27,28,45), primarily though their tissue repair and anti-inflammatory properties. Additionally, our previous study demonstrated that EndMT damaged endothelial tube formation capacity in an in vitro angiogenesis assay (46), which is consistent with our present results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically speaking, M2 macrophages should be pro-atherogenic due to their pro-angiogenic effects. However, the emerging understanding of macrophage subsets and their functions in atherosclerotic plaque has led to the consensus that M1 macrophages are pro-atherogenic, while M2 macrophages may promote plaque stability (27,28,45), primarily though their tissue repair and anti-inflammatory properties. Additionally, our previous study demonstrated that EndMT damaged endothelial tube formation capacity in an in vitro angiogenesis assay (46), which is consistent with our present results.…”
Section: Discussionmentioning
confidence: 99%
“…Classically activated M1 macrophages produce tumor necrosis factor (TNF), interleukin (IL)-6 and IL-1β, exacerbating the inflammatory response and promoting the development of atherosclerotic lesions (26). By contrast, alternatively activated M2 macrophages are an anti-inflammatory phenotype and have been reported to be protective in atherosclerosis (27,28). However, despite the central role of macrophages and foam cells in the development of atherosclerosis, their function in the process of EndMT has yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, myeloid deletion of GSK3α suppresses STAT1 phosphorylation in response to M1 activation through enhanced STAT3 phosphorylation and formation of STAT3:STAT1 heterodimers, whereas it promotes IL-4-dependent M2 phenotype through enhanced STAT6 phosphorylation. 67 The resulting phenotype is associated with an attenuation of atherosclerosis. 67 Cathepsin C was suggested to alter M1/M2 phenotype in vitro.…”
Section: Innate Immune Functionsmentioning
confidence: 99%
“…67 The resulting phenotype is associated with an attenuation of atherosclerosis. 67 Cathepsin C was suggested to alter M1/M2 phenotype in vitro. However, the mechanisms were unclear, and no changes of M1/M2 marker expression were detected in vivo in the absence of cathepsin C. 68 Heme uptake and degradation pathways are known to impact macrophage phenotype in vitro and in vivo.…”
Section: Innate Immune Functionsmentioning
confidence: 99%
“…Macrophages within atherosclerotic lesions of myeloid GSK3α-deficient mice, but not of GSK3β-deficient mice, displayed enhanced expression of the M2 markers and reduced expression of markers associated with M1 macrophage polarization; meanwhile GSK3α deletion, but not GSK3β deletion, attenuated the expression of genes associated with M1 polarization while promoting the expression of genes associated with M2 polarization by modulating STAT3 and STAT6 activation in bone marrow-derived macrophages, suggesting that the deletion of myeloid GSK3α attenuates the progression of atherosclerosis by promoting an M2 macrophage phenotype. 65 Also, to assess the role of Fcγ receptor IIb (FcγR IIb)-signaling in atherosclerosis, apolipoprotein E (ApoE) and FcγRIIb double knockout mice congenic to the C57BL/6 background ( Apoe –/– FcγRIIb B6 –/– ) were generated. These mice had smaller atherosclerotic lesions in the aortic root than those of Apoe –/– control mice.…”
Section: Introductionmentioning
confidence: 99%